Selecting, Teaching and Assessing Physical Education Dance Experiences. Issue 3 (24th March 2017) - Little, Stephanie; Hall, Tina
Abstract : Dance is a form of physical activity that can be enjoyed for a lifetime. Students at the elementary level benefit greatly from successful experiences in dance that lead to competency in various dance forms as well as an appreciation of personal expression through dance. Teaching dance, however, may not be comfortable or easy for beginning teachers, and perhaps even for experienced teachers. The purpose of this article is to provide physical education teachers with criteria for selecting developmentally appropriate, structured dances for elementary children as well as to provide tools for teaching and assessing these dance experiences. Specific dances appropriate for elementary-age children are provided along with a progression of dance steps from simple to complex that correspond with elementary grade levels.